Kepedulian Pekerja Penanganan Bahan di Supermarket X pada Ergonomi - guntarti tatik mulyati; Makhmudun Ainuri (Agricultural Faculty, 2017)
Manual material handling activities are still widely practiced in various industries, including supermarkets. Various products in supermarkets are moved with hand truck aids. This tool is used to ease of workers to avoid the risk of MSDs (musculoskeletal disorders) and LBP (low back pain). Workers' who concerns about work ergonomics, materials handling tools and their working environments can reduce the risk of MSDs and LBPs. In this paper we will examine how much the workers care about themselves, their tools, environment and their relation to work physiology of workers.Workers' concerns were identified using a Likert scale questionnaire with 5 scale of interest. Self-awareness is linked to an understanding of ergonomics, to hand tools used everyday and to the work environment. Occupational physiology is reflected in the pain experienced by workers as job impacts identified using Nordic Body Map (NBM), and work posture using OWAS (Ovako Working Posture Analysis System).The material handling worker assigned to move the product from supplier vehicle to warehouse or to showroom by hand truck. The survey results that the worker's concerned not so high on his ergonomics. The body map shows that before working the worker felt pain all over his body and got more pain after work. Worker's work posture varies substantially in category 1-2 which means that in this musculoskeletal system the work attitude results in significant tension influences requiring future improvement.